Molecular Epidemiology of Streptococcus pneumoniae Isolates from Children with Recurrent Upper Respiratory Tract Infections. - Izabela Korona-Glowniak; Maciej Maj; Radosław Siwiec; Artur Niedzielski; Anna Malm (PLoS ONE, 2016)
A total of 125 isolates were recovered from adenoids and/or nasopharynx of 170 children aged 2 to 5 from south-east Poland; they had undergone adenoidectomy for recurrent and/or persistent symptoms of upper respiratory tract infections. Pneumococcal isolates were analyzed by phenotyping (serotyping and antimicrobial resistance tests) and genotyping together with the clonality of the pneumococcal isolates based on resistance determinants, transposon distribution and multilocus sequence typing (MLST). Serotypes 19F, 6B and 23F constituted 44.8% of the isolates. Among all of the strains, 44.8% showed decreased susceptibility to penicillin and resistance to co-trimoxazole (52.8%), tetracycline (38.4%), erythromycin (53.6%), clindamycin (52.8%) and chloramphenicol (27.2%) was observed. Tn6002 was found in 34.8% of erythromycin-resistant isolates while composite Tn2010-in 16.7% of erm(B)-carrying isolates that harboured also mef(E) gene. Tn3872-related elements were detected in 27.3% of erythromycin-resistant strains. In the majority of chloramphenicol-resistant catpC194-carrying isolates (79.4%), ICESp23FST81-family elements were detected. The genotyping showed that pneumococcal population was very heterogeneous; 82 sequence types (STs) were identified, and the most frequent contributed to not more than 8% of the isolates. Nearly 44% STs were novel, each of them was recovered only from one child. Four STs belonged to one of the 43 worldwide spread resistant pneumococcal clones currently accepted by Pneumococcal Molecular Epidemiology Network (PMEN), i.e. Spain 9V-3, Spain 23F-1, Norway NT-42 and Poland 6B-20, accounting for 12 (16.7%) of the 75 nonususceptible isolates, and five STs were single-locus variants of PMEN resistant clones (England 14-9, Spain 9V-3, Spain 23F-1, Greece 21-30, Denmark 14-32), accounting 9 (12%) of nonsusceptible isolates. A few MDR clones belonging to 6B and 19F serotypes found among preschool children emphasizes rather the role of clonal dissemination of local strains in the community than international clones spreading in the increase of resistance among pneumococcal strains.